¿Cómo describir el proceso de escritura en los autógrafos de Calderón? Una taxonomía de las correcciones - Kroll, Simon (Anuario Calderoniano, 2015)
El presente trabajo propone un nuevo esquema de lectura para el análisis de autógrafos. Para poder describir el proceso de escritura con detalle se ha elaborado una taxonomía de correcciones siguiendo las fases de la producción de un discurso de la antigua escuela retórica. El artículo demuestra que clasificando las correcciones según la inventio, dispositio y elocutio se podrá determinar mejor qué fase de producción textual refleja el autógrafo por analizar. «How to Describe the Writing-process in Calderón’s Autographs? A Taxonomy of the Corrections» The present article proposes a new lector schema for the analysis of autographs. This schema presents a taxonomy of the corrections according to the stages of production of a discourse in ancient rhetoric: inventio, dispositio and elocutio. This taxonomy allows to describe Calderón’s writing process in a better way. Applying this taxonomy during the analysis of an autograph it should be possible to determine more precisely which phase of textual production the autograph in question reflects. PALABRAS CLAVE / KEYWORDS: Calderón, autógrafos, taxonomía, reelaboración, adaptación / Calderón, autograph, taxonomy, re-elaboration, adaptation.